Bhāī Jodha Siṅgha gadda saurabha : Bhāī Sāhiba dīāṃ dhāramika, widiaka, sabhiācārika, rājanītika te ātamaparaka likhatāṃ dā waragīkrita saṅgrahi - Jodha Siṅgha, 1882-1981; Piara Si?gha, 1914-1996 (Paṭiālā : Pabalīkeshana Biūro, Pañjābī Yūnīwarasiṭī, 1986)
Prose writings of a Panjabi litterateur.
In Panjabi.
Includes bibliographical references.
Keywords: Indo-Aryan philology; Indo-Aryan philology